Technological Innovations In the Humanities: A Study Of Its Impact On Nigeria’s Developmental Strides And Emerging - Innocent Nasuk Dajang; Mandong Mathias Ayuba; Samuel Mahanan (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The development of any society to a large extent depends on the degree of the security of lives and property of the citizens. A secure environment encourages intellectuals who are the drivers of nation-building; it also ensures national development. In recent years, Nigeria has been witnessing serious security threats that seem to have overwhelmed the nation’s security network and this has slowed down development in the country. This paper in light if these present realities, examined how technological innovations such as the integration of proper Information Communication Technology (ICT) resolve the emerging security threats bedeviling the country.  Integrating ICT in the humanities can help increase the rate of development in the country and also help resolve the emerging security threats bedeviling the country. Data for the paper was derived from a Focus Group Discussion (FGD) conducted via WhatsApp with fifteen selected academic staff who are in the humanities at the University of Jos. The data collected formed the basis of the discussion in the paper. The theoretical framework adopted is Computer-Assisted Language Learning (CALL) because it explains how technology can be utilized in language learning and evidently in the humanities to resolve challenging issues. The paper discovered that the humanities have not been fully integrated with ICT and have also not been effectively utilized in the quest for advancing development in Nigeria and resolving security challenges. The paper recommended amongst others the full integration of ICT in the humanities to expand the scope of the field to be utilized in resolving security challenges in the country.